2020
DOI: 10.1136/bmjopen-2019-032626
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation to improve pregnancy and perinatal outcomes: an overview of 42 systematic reviews

Abstract: ObjectiveTo review the evidence to assess effectiveness of vitamin D supplementation during pregnancy and associations of serum vitamin D levels with perinatal outcomes.DesignOverview of systematic reviews (SRs).Data sourcesSearches conducted in January 2019: Ovid Medline (1946–), Cochrane Library databases.Eligibility criteria for selecting studiesTwo reviewers independently screened titles and abstracts, and full texts using predefined inclusion criteria: SRs evaluating vitamin D supplementation in pregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 40 publications
3
21
1
2
Order By: Relevance
“…Thus, there is some evidence from observational studies about the associations between vitamin D serum levels and maternal outcomes, such as GDM development; however, an overview of several systematic reviews, examining effectiveness from RCTs on 25(OH)D supplementation, showed no effect in pregnancy (136).…”
Section: Nutritional Requirements and Role Of Nutraceuticals In Gdmmentioning
confidence: 99%
“…Thus, there is some evidence from observational studies about the associations between vitamin D serum levels and maternal outcomes, such as GDM development; however, an overview of several systematic reviews, examining effectiveness from RCTs on 25(OH)D supplementation, showed no effect in pregnancy (136).…”
Section: Nutritional Requirements and Role Of Nutraceuticals In Gdmmentioning
confidence: 99%
“…In this review, we focus on UFs and vitamin D, and not pregnancy. We included references for readers interested in the relationship between vitamin D, reproduction, and pregnancy [16,[76][77][78].…”
Section: Vitamin D and Uterine Fibroids-perinatal Implicationsmentioning
confidence: 99%
“…Similar findings have been reported in an umbrella review of meta-analyses of observational studies (16) . However, in an overview of forty-two systematic reviews, mixed results were presented for the associations between maternal vitamin D and LBW (17) . Current literature relating maternal vitamin D to birth weight is inconclusive.…”
mentioning
confidence: 99%